Calculation of Deexcitation Probability of Ne(3P2) by Ar for the Case E>>D - Khadka, Deba Bahadur (Journal of Nepal Chemical Society, 2013)
The deexcitaion probability calculation of the total Penning ionization cross section for Ne(3P2) by Ar has been made at collisional energy 38.1 meV. The comparison of deexcitationcross sections, polarizability, α/β , deexcitation probability, {IP(M)/IP(Ne*)}1/2 and the welldepth of interaction potentials for Ne(3P2) by Ar for the case E >> D has been made.DOI: http://dx.doi.org/10.3126/jncs.v30i0.9335Journal of Nepal Chemical Society Vol. 30, 2012 Page:  52-55 Uploaded date: 12/16/2013